Mount Lesiela (Kasieh) and Mount Patola (Saweli) on Seram Island Hold the Secret of Billions of Tons of Estimated Marble Reserves - Riry, Roberth Berthy; Salakory, Melianus (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
The Taniwel area is one of the regions on West Seram Island with significant marble potential, though it remains largely unknown to the general public. The marble potential in the Taniwel area includes Nakaela Mountain, as well as marbleized limestone at Mount Lesiela (Kasieh) and Mount Patola (Saweli) in Taniwel District, West Seram Regency. The purpose of this research is to estimate the marble reserves at Mount Lesiela (Kasieh) and Mount Patola (Saweli). The methods used in this study include reference/literature review, field investigation, laboratory analysis methods (AAS, Titrimetry, and Fire Assay), and data evaluation and analysis. The research results indicate that the estimated (possible) marbleized limestone reserves at Mount Lesiela (Kasieh) are 1,055,360,000 tons, and the estimated (possible) marbleized limestone reserves at Mount Patola (Saweli) are 68,640,000 tons.